The common link between sleep apnea syndrome and osteoarthritis: a literature review - Weng, Lian; Luo, Yuxi; Luo, Xiongjunjie; Yao, Kaitao; Zhang, Qian; Tan, Junjie; Yin, Yiran (Frontiers in Medicine, 2024)
Patients with Osteoarthritis (OA) often also suffer from Sleep Apnea Syndrome (SAS), and many scholars have started to notice this link, although the relationship between the two is still unclear. In this review, we aim to summarize the current literature on these two diseases, integrate evidence of the OA and OSA connection, explore and discuss their potential common mechanisms, and thus identify effective treatment methods for patients with both OA and SAS. Some shared characteristics of the two conditions have been identified, notably aging and obesity as mutual risk factors. Both diseases are associated with various biological processes or molecular pathways, including mitochondrial dysfunction, reactive oxygen species production, the NF-kB pathway, HIF, IL-6, and IL-8. SAS serves as a risk factor for OA, and conversely, OA may influence the progression of SAS. The effects of OA on SAS are underreported in the literature and require more investigation. To effectively manage these patients, timely intervention for SAS is necessary while treating OA, with weight reduction being a primary requirement, alongside combined treatments such as Continuous positive airway pressure (CPAP) and medications. Additionally, numerous studies in drug development are now aimed at inhibiting or clearing certain molecular pathways, including ROS, NF-KB, IL-6, and IL-8. Improving mitochondrial function might represent a viable new strategy, with further research into mitochondrial updates or transplants being essential.